MENINGKATKAN KREATIVITAS ANAK MELALUI MEDIA ALAT PERMAINAN EDUKTIF DI TAMAN KANAK-KANAK (TK) PEMBINA BANDAR LAMPUNG - Triyaningsih, Triyaningsih (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The purpose of this study was to determine the improvement of children's creativity through the media educative playing tools in Pembina Bandar Lampung Kindergarten. This research was conducted in August until October 2015. This study used action research (action research) models Kemmis and Mc. Taggard in the form of a spiral cycle consists of four stages: a) planning, b) measures, c) observations and d) reflection. The process of data collection is done through interviews, observation, and portfolios. The quantitative data of student outcome learning is a score of creativity performance with a rating scale. The results of the data analysis of the percentage increase in the initial assessment to cycle one are  27%. The first cycle to cycle two is 35%, from the initial assessment to the second cycle of 72%. The study concluded by using media educative playing tools ability increases children's creativity well.